Efficiency and equity in origin licensing to ensure complete DNA replication. (1st November 2021) - Mei, Liu; Cook, Jeanette Gowen
Abstract : The cell division cycle must be strictly regulated during both development and adult maintenance, and efficient and well-controlled DNA replication is a key event in the cell cycle. DNA replication origins are prepared in G1 phase of the cell cycle in a process known as origin licensing which is essential for DNA replication initiation in the subsequent S phase. Appropriate origin licensing includes: (1) Licensing enough origins at adequate origin licensing speed to complete licensing before G1 phase ends; (2) Licensing origins such that they are well-distributed on all chromosomes. Both aspects of licensing are critical for replication efficiency and accuracy. In this minireview, we will discuss recent advances in defining how origin licensing speed and distribution are critical to ensure DNA replication completion and genome stability.